2011
DOI: 10.4314/ejhs.v20i1.69429
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of HIV post-exposure prophylaxis use among health workers of governmental health institutions in Jimma Zone, Oromiya Region, Southwest Ethiopia

Abstract: BackgroundInfection with Human Immunodeficiency Virus is a serious public health problem costing the lives of many people including health workers. Hence, Ethiopia has developed guideline on the prevention of infection in health institutions in July 2004 and also employed the use of post exposure prophylaxis since the implementation of free antiretroviral in January 2005. However in the country, specifically in Jimma zone, published studies showing the clear picture about HIV post exposure prophylaxis in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
62
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 2 publications
(4 reference statements)
12
62
8
Order By: Relevance
“…This finding is concordant with another study done in Ethiopia, which showed that 72.0% of the respondents believed that PEP reduces the likelihood of HIV infection after exposure. 10 Self-learning and Internet/coworkers were the most common sources of information about PEP for respondents. Not even a single respondent had received the training on PEP of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is concordant with another study done in Ethiopia, which showed that 72.0% of the respondents believed that PEP reduces the likelihood of HIV infection after exposure. 10 Self-learning and Internet/coworkers were the most common sources of information about PEP for respondents. Not even a single respondent had received the training on PEP of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 61/83 (73.5%) and 57/83 (68.67%) did not take any antiretroviral (ARV) PEP for HIV and did not report their injury to their supervisor for immediate medical attention (Table II and III) despite there is ARV PEP and line of reporting system with assigned supervisor. 13,14 All these figures showed that infection prevention activities were neglected in Bahir Dar city administrative healthcare facilities. The healthcare workforce, 35 million people world wide, represents 12% of the working population.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to human blood and body fluids, placing them at risk of such blood born infections [2,3]. Accidental splash of blood and other body fluids into eyes, nose or mouth of HCWs is a critical problem in health care settings [4].…”
Section: Introductionmentioning
confidence: 99%